Reliability of Analytical Methods for Recombinant Human Insulin Quantification in the Bulk Crystals and in-Process Control - Angeliny Tamiarana Lima Tabosa, Heloísa Ribeiro Tunes de Sousa, Mauro Aparecido de Sousa Xavier, Elio Gomes Fernandes, Alessandra Rejane Ericsson de Oliveira Xavier, Luciano Vilela, Janete Maria da Silva Alves (Journal of Applied Pharmaceutical Science, 2018)
The aim of this study was to demonstrate the reliability of the protein determination methods used in the process of recombinant human insulin development before its scale up. The total protein content was measured by Bradford, molar extinction coefficient, and dry weight methods. The standards were analyzed using Mono-Q, Aquapore RP300, and Kromasil columns to calculate the concentrations of the proteins using the theoretical extinction coefficient and peak area. The following highly purified standards were used: batches B4-258 and QS009-010 of the sulfonated fusion protein; batches B4-267, B4-268, RALF-018, HGUT-042, HGUT-043, and HGUT-045 of the renatured fusion protein; the United States Pharmacopeia reference; and batch B4-253 of bulk insulin crystals. The results were analyzed using ANOVA or Student’s t-test at 95% significance. The Bradford method showed up to 60% variation for all evaluated standards, while the remaining two methods were consistent with each other. The chromatographic parameters were used to validate the analytical methods, and all results met the current guidelines of Brazilian regulatory agencies. The use of quality parameters and the statistical evaluation of the data demonstrated that analytical methods used in the in-process control are suitable for the intended purpose, which certifies the reliability of the generated data.
Keywords: Scale up, Bradford, molar extinction coefficient, dry weight, chromatograph.